Effect Of Watermelon Albedo Substutution On Quality Of Watermelon Jam - Ilpimayanti, Ilpimayanti; Anggraini, Ezi; Farqidah, Anni; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Jam is the result of processing of fruits obtained from the cooking process of fruit juice, puree or fruit pulp with the addition of several ingredients such as acids, sugar water and thickening agents. Jam is used as a filling for pastry products or as a complement in consuming bread. Jam is made from sugar, watermelon pulp, lime juice. This study aims to analyze the effect of 15%, 30% and 45% watermelon albedo substitution on the quality of color, aroma, texture and taste of watermelon jam produced. The type of research used in this research is pure experiment (True Experiment) with the research design used is a complete randomized design (RAL) with 3 repetitions. The type of data used is primary data obtained directly from 3 expert panelists by filling out the organoleptic test format. For hypothesis testing, this study uses statistical analysis of variance (ANOVA) test, if different will be tested with Duncan Multi Ranges Test (DMRT). The results showed that there was a significant effect on the quality of the texture of easy to spread, while the quality of color, aroma and soft texture, sweetness and watermelon flavor did not have a significant difference in watermelon albedo substitution. From this statement it can be concluded that in the indicators of color quality, aroma and soft texture, sweetness and taste of watermelon Ho is accepted because f count, < f table. While in the quality of mudsh texture in the smear Ho is rejected because f count> f table. The best research results are in the best watermelon albedo substitution in treatment 2, namely 30% watermelon albedo